1999
DOI: 10.1002/(sici)1098-2736(199904)36:4<431::aid-tea3>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ecology fieldwork and student attitudes toward environmental protection

Abstract: This article is a summary of research carried out on Spanish secondary school students 14 -16 years of age, with the intention of finding out what contributions fieldwork makes toward the understanding of concepts and principles of ecology, and also to ascertain the effects of fieldwork on the defense of the studied ecosystem. Before further research was conducted, an exploratory study was carried out consisting of an initial diagnosis of the pupils' ideas; fieldwork materials were prepared and an ecology unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…Louv (2005, p. 150) reports that, "The childhoods of environmentalists and naturalists are replete with stories of their childhood inspiration, leading directly to their later activism." It has been shown that middle and high school aged students that participate in fieldwork-based environmental programs, led by scientists, have a greater sense of environmental stewardship and will likely live more sustainably (Manzanal et al 1999;Crawford 2000;Taylor et al 2008;Johnson and Catley 2009). As discussed above, there are a number of project-based case studies demonstrating the success of improving stewardship attitudes in students.…”
Section: Students As the Targeted Groupmentioning
confidence: 76%
See 2 more Smart Citations
“…Louv (2005, p. 150) reports that, "The childhoods of environmentalists and naturalists are replete with stories of their childhood inspiration, leading directly to their later activism." It has been shown that middle and high school aged students that participate in fieldwork-based environmental programs, led by scientists, have a greater sense of environmental stewardship and will likely live more sustainably (Manzanal et al 1999;Crawford 2000;Taylor et al 2008;Johnson and Catley 2009). As discussed above, there are a number of project-based case studies demonstrating the success of improving stewardship attitudes in students.…”
Section: Students As the Targeted Groupmentioning
confidence: 76%
“…Respect for the environment is exhibited by awareness of personal impacts made to the environment, feelings of frustration when the environment is negatively impacted, and concern about environmental health and condition (Manzanal et al 1999;Ryan et al 2001;Kenney et al 2003;Bodzin 2008;Cook 2008;Stern et al 2008).…”
Section: Areas Of Environmental Stewardshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating ecosystem roles as particular solution of environmental problem initiated student awareness about their environment by previously understood the function of each component and the effect of ecosystem absence in an area thought it need to be proven by further studies. These occurrences strengthened [7] note that outdoor activity assists student to clarify ecology concept and direct participation in forming vary of attitude in determining ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Incluimos en la muestra los trabajos de Cutter (1993), Mick (1996), Manzanal, Rodríguez y Casal (1999) y Rodrigo et al (1999), dada su relevancia destacada en el reporte realizado en Amórtegui y Correa (2012) como estudios específicos sobre el trabajo de campo en la enseñanza de la Biología y/o la formación del profesorado de esta disciplina. Del universo de revistas, tres corresponden específicamente a la enseñanza de la Biología (Journal of Biological Education, The American Biology Teacher y Revista Biografía: Escritos sobre la Biología y su enseñanza).…”
Section: Metodologíaunclassified